2022
DOI: 10.3390/ijerph19042262
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Contextual Problems and Sensation Seeking in the Association between Substance Use and Mental Health in Adolescents from Northern Chile

Abstract: Substance use is a risk behavior that has been associated with adverse mental health outcomes in adolescence. The aim of this study was to determine the relation between behavioral problems, emotional problems, and substance use as well as the mediating role of contextual problems and sensation seeking in this relation. A cross-sectional study of 2277 adolescents from Northern Chile was conducted. The System for the Evaluation of Children and Adolescents (SENA) was used to assess substance use, contextual prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Thus, as other studies have shown, positive family functioning is beneficial in adolescence as it mediates the problematic use of social networks and increases perceived social support [18,19]. There is a need to promote prosocial behaviours in order to reduce disruptive and health-risk behaviours in young people and increase their self-esteem and personal well-being [7][8][9][10]27,28]. Such a positive relationship has also been found between family functioning and school climate, which is linked to subsequent studies indicating that young people from dysfunctional families have problems at school [32].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, as other studies have shown, positive family functioning is beneficial in adolescence as it mediates the problematic use of social networks and increases perceived social support [18,19]. There is a need to promote prosocial behaviours in order to reduce disruptive and health-risk behaviours in young people and increase their self-esteem and personal well-being [7][8][9][10]27,28]. Such a positive relationship has also been found between family functioning and school climate, which is linked to subsequent studies indicating that young people from dysfunctional families have problems at school [32].…”
Section: Discussionmentioning
confidence: 98%
“…This period stands out for the vulnerability of young people and their desire to experience new sensations together with social influences and peer pressure [6]; the most commonly used coping strategies are avoidance and social support [7]. This search for new sensations may lead adolescents to engage in activities that involve risky behaviour, such as drug use [8], perpetuation of violence [9] or unsafe sexual behaviours, which have negative consequences such as sexually transmitted infections or unwanted pregnancies [10]. These risky behaviours can cause mental or physical harm and, if not identified early, young people's health and their family and social bonds can be severely damaged [11,12].…”
Section: Introductionmentioning
confidence: 99%